Laser-backscattering imaging for characterising the dairy matrix in different phases during curd processing. (October 2021) - Verdú, Samuel; Perez, Alberto J.; Barat, José M.; Grau, Raúl
Abstract: The capability of laser-backscattering imaging technique as a non-destructive method to control the effect of fat on curdling process phases was studied. It was based on capturing images of the diffraction patterns generated by a laser-matrix interaction, from which data were acquired. The studied phases were: raw material inspection; curdling monitoring; fresh curd inspection and curd storage monitoring. Milk was used with three different fat contents (0, 1.5 and 3.5%). An extra category of 1.5% fat without lactose was added to test the effect of modification on other compounds. All the phases were characterised by a destructive analysis (rheology, texture profile analysis, syneresis) to study both the evolution of the physical properties during the process and the relation to imaging data. Images successfully captured the variance generated by fat content and physical modifications. Differences in fat content were distinguished for raw material and fresh curd despite lack of lactose. Curdling monitoring also allowed the fat effect to be characterised and coagulation time to be established. Matrix evolution during storage was modelled from imaging for 24 h and 96 h. Imaging data correlated with syneresis evolution and texture features. The obtained results showed that laser-backscattering imaging was capable of capturing the effect of both fat and physical changes on each processing phase, which implies that this technique can be employed as a common system for independent phase control. Highlights: The capability of laser-backscattering imaging to control curd processing was studied. The phases were: raw material inspection; curdling; curd inspection and storage. Imaging data correlated with rheology, texture and syneresis of three fat contents.